The scope of conflict in international merger control - Damien J. Neven; Lars-Hendrik Röller (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
In this paper, we analyse the scope for conflict between national merger control agencies which assert jurisdictions simultaneously. We consider a positive model of merger control in which market definition and the analysis of dominance are both explicitly specified. We find that conflict in international merger control is less likely to occur when economic integration is high. Hence, “globalisation” should alleviate rather than exacerbate conflict. In addition, we observe that conflict is less likely to arise between countries of different size and for extreme policy rules (very lenient or very strict) towards dominance. – – In diesem Beitrag werden die Konfliktpotentiale zwischen Kartellbehörden untersucht. Die Analyse basiert auf einem positiven Ansatz der Fusionskontrolle, in dem die Kartellbehörde explizit modelliert wird. Es zeigt sich, daß Konflikte bei der internationalen Fusionskontrolle weniger wahrscheinlich sind, wenn Unternehmen auf integrierten Märkten konkurrieren. In diesem Sinne führt eine ,,Globalisierung“ der Weltwirtschaft zu einer Reduzierung des Konfliktpotentials zwischen Wettbewerbsbehörden.
Keywords: 330